2021
DOI: 10.1186/s12960-021-00691-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the performance of community health volunteers working within urban informal settlements in low- and middle-income countries: a qualitative meta-synthesis review

Abstract: Background There is limited information on community health volunteer (CHV) programmes in urban informal settlements in low- and middle-income countries (LMICs). This is despite such settings accounting for a high burden of disease. Many factors intersect to influence the performance of CHVs working in urban informal settlements in LMICs. This review was conducted to identify both the programme level and contextual factors influencing performance of CHVs working in urban informal settlements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…; https://doi.org/10.1101/2023.03. 22.23287562 doi: medRxiv preprint to Kok and colleagues, programme design factors are features of the programme or intervention design that have a direct influence on CHVs' performance and can be directly modified and adjusted to motivate maximum CHV performance (20). They include renumeration, recruitment, supervision and workload, community and health system links, and resources and logistics (2).…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
See 2 more Smart Citations
“…; https://doi.org/10.1101/2023.03. 22.23287562 doi: medRxiv preprint to Kok and colleagues, programme design factors are features of the programme or intervention design that have a direct influence on CHVs' performance and can be directly modified and adjusted to motivate maximum CHV performance (20). They include renumeration, recruitment, supervision and workload, community and health system links, and resources and logistics (2).…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…; https://doi.org/10.1101/2023.03. 22.23287562 doi: medRxiv preprint highlighted above, a systematic review by Ogutu et al, (22) showed that specific to UIS in LMICs, some of the factors that negatively impacted on the performance of CHVs at the broader contextual level in UIS included insecurity and the demand for material or financial support by households.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we investigated the emergency response and healthy community construction of informal settlements, focussing not only on the importance of the local government, 25 the involvement of community volunteers 38 and the underlying wisdom of the dwellers, 11 but also on the epidemic response and interaction process of informal settlements, which have received less attention in previous research. In particular, we aimed to investigate the following: (1) How are the different participants in informal settlements, such as the local government, community committees and tenants, affected by COVID-19?…”
Section: Introductionmentioning
confidence: 99%
“…Governance, leadership and management processes are critical: studies have looked specifically at the role of supportive supervision [12,13], performance management, evaluation and feedback [14] concern for workers' welfare by hospital management [15], as well as resource availability [14]. While a number of studies have focused on the importance of social identity, respect, and community support for community health workers [16][17][18], the study of social and professional identity and respect among front-line workers in low-and middle-income hospital settings is limited [19].…”
mentioning
confidence: 99%